The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.15446/ga.v20n1.58681
|View full text |Cite
|
Sign up to set email alerts
|

Comportamientos proambientales de los empleados de la hotelería. El caso de un hotel certificado en Huatulco, México

Abstract: Cada vez son más las empresas que asumen acciones a favor del ambiente, entre las más comunes se encuentran la adopción de sistemas de gestión ambiental o esquemas de certificación ecológica, no solo porque les permite gestionar de manera más eficiente sus recursos y disminuir sus costos haciéndolas más rentables, sino porque también les mejora su imagen pública y las compromete con la sociedad y la naturaleza. En el caso del destino turístico de Bahías de Huatulco, se han iniciado actividades orientadas a la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Another great challenge is ecological behaviour itself. Some authors found significant relationships between PEB, and motives and knowledge [53], the values and environmental knowledge of hotel employees in Mexico [54], the anthropomorphic perception of nature [55,56] and the sense of guilt for environmental degradation [57], perceived values and felt responsibility [58]; CSR practices and employee performance at work [59] and in the confidence, identification, well-being, autonomous, and controlled motivation and environmental concerns of hotel employees in China [60,61]; attitudes towards environmental problems and sociodemographic variables [62], and the active leadership of supervisors in Russia [63].…”
Section: Influence Of Csr Practices On Worker Pebmentioning
confidence: 99%
“…Another great challenge is ecological behaviour itself. Some authors found significant relationships between PEB, and motives and knowledge [53], the values and environmental knowledge of hotel employees in Mexico [54], the anthropomorphic perception of nature [55,56] and the sense of guilt for environmental degradation [57], perceived values and felt responsibility [58]; CSR practices and employee performance at work [59] and in the confidence, identification, well-being, autonomous, and controlled motivation and environmental concerns of hotel employees in China [60,61]; attitudes towards environmental problems and sociodemographic variables [62], and the active leadership of supervisors in Russia [63].…”
Section: Influence Of Csr Practices On Worker Pebmentioning
confidence: 99%